Brush-Painting and Photonic Sintering of Copper Oxide and Silver Inks on Wood and Cardboard Substrates to Form Antennas for UHF RFID Tags - Erja Sipilä; Johanna Virkki; Jianhua Wang; Lauri Sydänheimo; Leena Ukkonen (International Journal of Antennas and Propagation)
Additive deposition of inks with metallic inclusions provides compelling means to embed electronics into versatile structures. The need to integrate electronics into environmentally friendly components and structures increases dramatically together with the increasing popularity of the Internet of Things. We demonstrate a novel brush-painting method for depositing copper oxide and silver inks directly on wood and cardboard substrates and discuss the optimization of the photonic sintering process parameters for both materials. The optimized parameters were utilized to manufacture passive ultra high frequency (UHF) radio frequency identification (RFID) tag antennas. The results from wireless testing show that the RFID tags based on the copper oxide and silver ink antennas on wood substrate are readable from ranges of 8.5 and 11 meters, respectively, and on cardboard substrate from read ranges of 8.5 and 12 meters, respectively. These results are well sufficient for many future wireless applications requiring remote identification with RFID.